PENGARUH ORIENTASI PELANGGAN, NILAI YANG DIRASAKAN, DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA UMKM KULINER KECAMATAN SUMBAWA - Aldy Kurniawan Saputra; Abdul Salam (Publika Citra Media, 2026)
This study aims to examine the influence of customer orientation, perceived value, and customer satisfaction on customer loyalty in culinary micro, small, and medium enterprises (MSMEs) in Sumbawa District. The research is motivated by the rapid growth of culinary MSMEs and increasingly intense competition, which require businesses to focus on customer retention strategies. This study used a quantitative associative approach. Data were collected through questionnaires distributed to 112 consumers of culinary MSMEs using a purposive sampling technique. The data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results indicate that customer orientation has a positive and significant effect on customer loyalty. Perceived value also shows a positive and significant influence on customer loyalty. In addition, customer satisfaction has a positive and significant effect on customer loyalty. These findings suggest that understanding customer needs, creating value that meets customer expectations, and providing consistent satisfaction play an important role in building and maintaining customer loyalty in culinary MSMEs.